PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) DENGAN MEDIA MOLYMOD TERHADAP HASIL BELAJAR KIMIA - Nur Azmiati; Miterianifa Miterianifa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This research was a quasi-experiment—instigated by the low of students’ chemistry achievement. This research aimed at knowing the effect of using Team Games Tournament (TGT) type of Cooperative Learning Model with Molymod media tomard students’ achievement of X grade at Senior High School of YLPI Pekanbaru. The samples of this research were Random Sampling comprising 2 classes—X1 (Experimental group) and X3 (Control group). There were 4 meetings done. Test, interview, questionnaire, and documentation were the techniques of collecting the data. T-test formula was used to find out the result of students’ achievement. Based on the data analysis, it can be stated that tobserved was 4.14 and ttable 2.00 and it showed that tobserved was higher than ttable. It revealed that Ho was rejected and Ha was accepted. In other words, there was a significant effect of using Team Games Tournament (TGT) type of Cooperative Learning model with Molymod media toward students’ achievement of X grade at Senior High School of YLPI Pekanbaru with coefficient effect 20%. Keywords: Team Games Tournament (TGT) of Cooperative Learning Model, Molymod Media, Achievement.